S71 Reductions in cystic fibrosis lung infection with long-term ivacaftor treatment: a cohort study utilising data from the UK CF registry. (December 2018) - Frost, F; Nazareth, D; Walshaw, MJ
Abstract : Introduction: Ivacaftor can greatly improve clinical outcomes in people with cystic fibrosis and has been shown to have in-vitro antibacterial properties, yet the long-term microbiological outcomes of treatment are largely unknown. Methods: We undertook a matched retrospective cohort study utilising data from the UK CF Registry for the time period 2011–2016. Incident ivacaftor users in 2013 who were still receiving it in 2016 were matched to up to 5 never-users based on index demographics and microbiology status in 2012. Matching and analysis were performed separately for each CF pathogen. Prevalence of positive respiratory cultures were recorded and annual relative risk was calculated using a generalised linear model with binomial error distribution. Results: Inclusion criteria for the ivacaftor group was met in 274 cases and they were matched to 1329 similar individuals with comparable index S. aureus status, 1334 with for P. aeruginosa, 1336 for Aspergillus spp. and 1184 for Burkholderia cepacia complex (BCC). Groups were well matched at baseline. In 2014 (one year after initiation) ivacaftor use was associated with significantly reduced P. aeruginosa (RR 0.72 [0.58–0.89], p=0.003) and this effect continued throughout the study period see figure 1. For S. aureus there was no change after the first year of treatment (RR 1.00 [0.80–1.25], p=0.99), however in the subsequent two years there were significant reductions (2015: 0.61 [0.45–0.82], p<0.0001. 2016: OR 0.73 [0.55–0.97], p=0.02). Similarly no effects in Aspergillus spp . were observed in 2014 but by 2016 there were significant reductions (RR 0.30 [0.17–0.51], p<0.001). No changes in BCC were observed. Multivariate analysis confirmed reductions in P. aeruginosa were independent of changes in the number of samples submitted annually. Conclusions: We found that ivacaftor use is associated with a reduced likelihood of a positive respiratory culture for P. aeruginosa, S. aureus and Aspergillus spp. The more pronounced effects we observed against P. aeruginosa are in contrast to in-vitro studies of ivacaftor's innate antimicrobial properties. Hence, the changes in respiratory microbiology after ivacaftor initiation observed here and in other real-world studies are likely related CFTR-restoration rather than a direct bactericidal effect from ivacaftor itself.